Republic of the Marshall Islands : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Informational Annex highlights the Marshall Islands' existing tax system's inability to raise additional revenue, discouragement of private investment, and inequitability. Careful consideration needs to be given to the potential of a comprehensive tax reform program, including strengthening tax administration, for raising additional revenue while supporting the private sector. Many state-owned enterprises (SOEs) are a drain on public finances, and their unreliable or costly services undermine private sector development. To improve their performance, reforms are needed to strengthen efficiency, better delineate commercial and noncommercial services, and introduce tariff systems that better reflect cost of services. In areas where SOEs provide purely commercial services, divestment should be considered.